Applying Contextual Teaching and Learning on Multimedia to Enhance Logical Thinking Skills - Eka Fitrajaya Rahman; Almira Kiasati Solehudin; Erna Piantari (CCIT Journal, 2023)
Contextual teaching and learning is a learning concept that encourages students to make a connection between knowledge and its application in real life. This concept can stimulate students to think logically so that they can improve their logical abilities. By having good logic skills, students will find it easier to solve various problems that occur. To facilitate the learning process based on contextual teaching and learning, in this research, web-based multimedia learning was developed by applying the Contextual teaching and learning model with the ADDIE method. From the results of the research conducted, it was found that the increase in students' logical abilities was evaluated based on three indicators: the coherence of thinking with a value of n-gain = 0.32 (moderate improvement), argumentative ability n-gain = 0.27 (low improvement), and drawing conclusions n-gain = 0.33 (moderate improvement).